2021
DOI: 10.3390/ijms222312872
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Protein Expression and Promoter Methylation in Ovarian Cancer: A Strong Prognostic Value with Theranostic Promises

Abstract: Ovarian cancer (OC) is the deadliest among all gynecological cancers. Epidemiological studies showed that obesity might influence many cancers including OC. One of the key factors that may link obesity and OC is leptin (LEP), known as an adipokine with pleiotropic effects on body homeostasis. This study aims to investigate the expression pattern of LEP, assess the methylation profiles of LEP and their associations with clinicopathological features including survival outcomes of OC patients. The protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…This was also supported by the findings that a chronic low level of inflammation is associated with obesity, and contributes to BC by damaging the DNA [44]. Moreover, cell proliferation in BC is due to the production of excessive amounts of estrogen and adipokines from fat cells [43,45,46].…”
Section: Discussionmentioning
confidence: 62%
“…This was also supported by the findings that a chronic low level of inflammation is associated with obesity, and contributes to BC by damaging the DNA [44]. Moreover, cell proliferation in BC is due to the production of excessive amounts of estrogen and adipokines from fat cells [43,45,46].…”
Section: Discussionmentioning
confidence: 62%
“…Its best-known biological role is to signal satiety to the hypothalamus and subsequently reduce food intake and fat storage. Leptin was shown to promote cancer progression and metastasis by regulating the EMT, cell adhesion to the extracellular matrix (ECM), and proteolysis of the ECM compounds [ 59 , 60 ]. Although leptin’s expression is common in most OC cells and is associated with higher aggressiveness and poorer treatment outcome [ 59 , 60 ], circulating leptin levels are usually lower in presence of OC compared to benign tumors [ 28 , 29 , 61 , 62 ], as could also be observed in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…As in breast and endometrial cancer, leptin has been studied in relationship to cancer progression, metastases, and chemoresistance in ovarian cancer 141,142 . Isolated studies have identified leptin as a biomarker for disease although further randomized assessments are needed to validate these findings 143,144 . Leptin signaling via the JAK/STAT3 pathway upregulates ERα transcriptional activation, mediating ovarian cancer progression 141 .…”
Section: Methodsmentioning
confidence: 99%